Determining Factors of Child Begging on the Streets of the Cities of Puno and Juliaca, 2023 - Maquera-Maquera, Yuselino; Zuniga-Vasquez, María Emma; Maquera-Maquera, Yanet Amanda; Alanoca-Arocutipa, Vicente; Quenta, Rolando Cáceres; Apaza-Ticona , Jorge; Chata-Quispe, Luz Mery (Journal of Ecohumanism, 2024)
Extreme poverty has devastating consequences that are closely linked to living conditions. Begging has become an alternative for family support and children resort to a set of survival strategies on the street. The objective was to establish the determining factors of the begging condition of street children in the cities of Puno and Juliaca. The methodology was oriented from the mixed approach, descriptive design, the selected population was 20 children who beg in crowded places in the cities of Puno and Juliaca. The techniques used were: the standardized questionnaire, the in-depth interview guide, structured survey and participatory observation. Data analysis was done with Stata and Atlas Ti. The results were as follows: The begging factors in children are directly related to the extreme poverty of the family unit, by identifying more than three unsatisfied basic needs. The presence of tuberculosis and other diseases, as well as the presence of a disability in a family member, are the factors that force children to go out into the streets, some to sell products and beg, earning an average income of ten soles per day (three dollars) that is used to support the family. These children are not covered by social programs (Qali Warma, PVL, School Breakfasts).